An iterative approach to cis-oligodiacetylenes - Kosinski, Christoph; Hirsch, Andreas; Heinemann, Frank Wilhelm; Hampel, Frank (European Journal of Organic Chemistry, 2001)
Phenyl-terminated cis-oligodiacetylenes such as 18, containing a π-conjugated backbone with four triple and three double bonds, were synthesized using Pd-catalysed Sonogashira coupling reactions. Compound 18 represents the longest cis-oligoenyne system to date, but it suffers from the drawback of cis/trans isomerization observed in solution. In order to avoid cis/trans isomerization in such cis-oligodicacetylenes, the ene moieties within the oligomeric backbone were locked by incorporation into ring systems. 1,2-Dibromocyclopentene was used as an olefinic building block for this purpose, permitting the iterative synthesis of the cis-oligodiacetylenes 27 and 28, possessing the same π-conjugated backbone as 18. Unlike that compound, however, 27 and 28 are stable both in solution and in the solid state. Whereas X-ray crystallography revealed a completely planar structure for 27 in the single crystal, NMR and computational investigations suggest that a preferred helical conformation is likely in solution.